What Is the Risk of Anal Carcinoma in Patients With Anal Intraepithelial Neoplasia III?. Issue 12 (December 2018) - Lee, Grace C.; Kunitake, Hiroko; Milch, Holly; Savitt, Lieba R.; Stafford, Caitlin E.; Bordeianou, Liliana G.; Francone, Todd D.; Ricciardi, Rocco
Abstract : BACKGROUND: The risk of anal carcinoma after previous diagnosis of anal intraepithelial neoplasia III is unclear. OBJECTIVE: The purpose of this study was to estimate the risk of anal carcinoma in patients with anal intraepithelial neoplasia III and to identify predictors for subsequent malignancy. DESIGN: This was a retrospective review using the Surveillance, Epidemiology, and End Results registry (1973–2014). SETTING: The study was composed of population-based cancer registries from the United States. PATIENTS: Patients who were diagnosed with anal intraepithelial neoplasia III were included. MAIN OUTCOME MEASURES: The primary outcome was rate of subsequent anal squamous cell carcinoma. Predictors for anal cancer were identified using logistic regression and Cox proportional hazard models. RESULTS: A total of 2074 patients with anal intraepithelial neoplasia III were identified and followed for a median time of 4.0 years (interquartile range, 1.8–6.7 y). Of the cohort, 171 patients (8.2%) subsequently developed anal cancer. Median time from anal intraepithelial neoplasia III diagnosis to anal cancer diagnosis was 2.7 years (interquartile range, 1.1–4.5 y). Fifty-two patients (30.4%) who developed anal carcinoma were staged T2 or higher. Ablative therapies for initial anal intraepithelial neoplasia III were associated with a reduction in the risk of anal cancer (OR = 0.3 (95% CI, 0.1–0.7); p = 0.004). Time-to-event analysis revealed that the 5-year incidence of anal carcinoma after anal intraepithelial neoplasia III was 9.5% or ≈1.9% per year. LIMITATIONS: The registry did not record HIV status, surveillance schedule, use of high-resolution anoscopy, or provider specialty. CONCLUSIONS: In the largest published cohort of patients with anal intraepithelial neoplasia III, ≈10% of patients were projected to develop anal cancer within 5 years. Nearly one third of anal cancers were diagnosed at stage T2 or higher despite a previous diagnosis of anal intraepithelial neoplasia III. Ablative procedures were associated with a decreased risk of cancer. This study highlights the considerable rate of malignancy in patients with anal intraepithelial neoplasia III and the need for effective therapies and surveillance. SeeVideo Abstract athttp://links.lww.com/DCR/A764 . Abstract : Supplemental Digital Content is available in the text.